1989
DOI: 10.1099/00222615-30-4-285
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Pseudomonas aeruginosa to respiratory epithelium and the effect of leucocyte elastase

Abstract: Summary. The tracheobronchial secretions from patients with cystic fibrosis often contain high amounts of free proteases. To evaluate whether human leucocyte elastase (HLE) can favour the persistence of bacterial airways infection, we exposed the frog palate mucosa to HLE and then to radiolabelled Pseudomonas aeruginosa and followed the sequence of events by scanning electronmicroscopy. In response to HLE there was a marked outpouring of mucus and a desquamation of the epithelium. P. aeruginosa was shown to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Thus, DNA-attached MPO might promote proinflammatory responses by catalyzing the production of hypochlorous acid and downstream-chlorinated amine compounds, as well as by enhancing neutrophil activation status and survival. The high local concentration of MPO on the biofilm and the augmented neutrophil Mac-1 expression, by increasing inflammation, might contribute to bacterial killing as well as to damage to the surrounding tissues, as previously proposed (61).…”
Section: Discussionsupporting
confidence: 60%
“…Thus, DNA-attached MPO might promote proinflammatory responses by catalyzing the production of hypochlorous acid and downstream-chlorinated amine compounds, as well as by enhancing neutrophil activation status and survival. The high local concentration of MPO on the biofilm and the augmented neutrophil Mac-1 expression, by increasing inflammation, might contribute to bacterial killing as well as to damage to the surrounding tissues, as previously proposed (61).…”
Section: Discussionsupporting
confidence: 60%
“…Adherence of a nonmucoid strain of P. aeruginosa to the tracheal collagen layer was also found in rat trachea injured by brushing [43]. PLOTKOWSKI and co-workers [14,44,45] have also reported adherence of nonmucoid P. aeruginosa to type I collagen matrix [14], and to submucosal connective tissue obtained from the frog palate [44,45].…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, it has been clearly shown that injured repiratory epithelium is highly susceptible to P. aeruginosa adherence [26,27]. Desquamated cells [29], as well as the denuded extracellular matrix (ECM) [26,30], and in particular components of the ECM, including fibronectin [31] and laminin [32], either belonging to the basement membrane or secreted [30] in the extracellular milieu, represent preferential targets for P. aeruginosa attachment.…”
Section: Pseudomonas Aeruginosa Adherence To Respiratory Epitheliummentioning
confidence: 99%